2008
DOI: 10.1002/pen.21152
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of residual stress and viscoelastic deformation of film insert molded parts

Abstract: Film insert molding (FIM) has been modeled numerically to predict residual stress and viscoelastic deformation of the part. Nonisothermal three dimensional flow analysis for filling, packing, and cooling stages was carried out by using a commercial software. It was assumed that the inserted film was solid throughout the entire molding procedure although remelting could occur at the interface with the substrate. The flow analysis results, e.g., temperature, stress, and density distribution in the substrate doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…It is well known that thermal shrinkage and residual stresses play an important role in predicting the thermoviscoelastic deformation of final FIM products composed of two polymeric parts [24, 25]. Therefore, thermal shrinkage and residual stresses of the biaxially drawn film should be investigated to perform thermoviscoelastic stress analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that thermal shrinkage and residual stresses play an important role in predicting the thermoviscoelastic deformation of final FIM products composed of two polymeric parts [24, 25]. Therefore, thermal shrinkage and residual stresses of the biaxially drawn film should be investigated to perform thermoviscoelastic stress analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Frequently, cited studies [2–4] reported that other processing defects, e.g., undesired creases, folded lines, and severe warpage, were generated at the near weld‐line region when high shear rate was applied to FIM process. It has also been reported that unusual problems were observed due to thermal conductivity difference between the solid film and the molten resin during FIM and asymmetric residual stresses over the film and substrate regions [5–7].…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of the dissolved blowing agent (carbon dioxide) is assumed to be always equal to the equilibrium concentration and the rest of the blowing agent is immediately evaporated into bubbles. The second more general bubble‐shell model , also includes the effect of diffusion limitation. Recently, Karimi and Marchisio proposed a model, which can predict the evolution of the foam density, temperature, and bubble size distribution using the population balance equation and successfully coupled it with bubble‐shell model of Ferkl et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although the thermal stability and mechanical properties of the thermosetting CFFRC produced by RTM are excellent because the cured thermoset resins are never remelted, a long curing time is required and recycling is not permitted. For IM, molten thermoplastic resins are injected after the CFF is appropriately located in the metal mold, and then, the injected resins are rapidly cooled . This processing provides the advantage of easy shaping for various applications and recycling of the produced thermoplastic CFFRC.…”
Section: Introductionmentioning
confidence: 99%